Co-curable poly(glycidyl methacrylate)-grafted graphene/epoxy composite for thermal conductivity enhancement. (21st November 2019) - Oh, Hyunwoo; Kim, Youjin; Kim, Jooheon
Abstract: Thermally conductive epoxy composite is prepared by directly incorporated graphene into the matrix. The 3-methacryloyloxypropyltriethoxysilane (MPTES) functionalized reduced graphene oxide (MRGO) is synthesized by a sol-gel reaction followed by chemical reduction, leading to the introduction of methacrylate groups with carbon-carbon double bonds. Then, radical copolymerization is employed to afford poly(glycidyl methacrylate) grafted MRGO, which can react with amine groups in the curing agent, 4.4′-diaminodiphenylmethane. The exothermic peaks were observed for the epoxy composites revealed that p-MRGO is co-cured with the curing agent and incorporated into the matrix. The thermal conductivity of the p-MRGO/epoxy composites reaches 0.75 W m −1  K −1 at p-MRGO content of 7 wt%, corresponding to a thermal conductivity enhancement of 249% Furthermore, the crosslinking density is calculated to confirm the co-curing effect of p-MRGO. Our results demonstrated that the covalent bond between the filler and matrix is an advantageous approach for improving the thermal conductivity of epoxy composites. Graphical abstract: Image 1 Highlights: Copolymerized MPTES and PGMA chains are introduced on the graphene surface. p-MRGO is directly incorporated into the matrix with co-curing reaction. p-MRGO/epoxy composite exhibits high thermal conductivity enhancement. The crosslinking densities of composites are affected by p-MRGO contents.